2001
DOI: 10.1524/ract.2001.89.1.059
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic reduction of pertechnetate (99TcO4 -) insimulated alkaline nuclear wastes

Abstract: Technetium / Nuclear waste / Fission products / Catalytic reduction / Hanford siteSummary. Pertechnetate ion ( 99 TcO 4 − , 10 −4 M) in alkaline solution is quantitatively reduced to hydrous TcO 2 by thermolysis (65 • C, 4 days) in the presence of organic complexants and fission-product noble metals (RuCl 3 , RhCl 3 , and PdCl 2 ; 0.001 M). Over 99% reduction occurs in the presence of ethylenediaminetetraacetic acid (EDTA), hydroxyethyl(ethylenediaminetriacetic acid) (HEDTA), or glycolic acid (0.050 M). Nitril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 9 publications
(6 reference statements)
0
23
0
Order By: Relevance
“…The use of irradiation in these experiments does not imply a similar mechanism for reduction of TcO 4 -in high-level waste tanks. Both chemical (Bernard, Bauer et al 2001) and radiolytic ) pathways exist for reduction of TcO 4 -under these conditions, but the radiation-chemical pathway is different from the pathway that is operative here, direct reduction of TcO 4 -by hydrated electrons from the radiolysis of water.…”
Section: Introductionmentioning
confidence: 71%
“…The use of irradiation in these experiments does not imply a similar mechanism for reduction of TcO 4 -in high-level waste tanks. Both chemical (Bernard, Bauer et al 2001) and radiolytic ) pathways exist for reduction of TcO 4 -under these conditions, but the radiation-chemical pathway is different from the pathway that is operative here, direct reduction of TcO 4 -by hydrated electrons from the radiolysis of water.…”
Section: Introductionmentioning
confidence: 71%
“…It has been shown that in the presence of the noble metals (ruthenium, rhodium, and/or platinum), alkaline pH, elevated temperatures, and organic molecules, catalytically active metals are formed that are capable of reducing pertechnetate (Bernard et al 2001). The catalytically active metals in the presence of hydrogen only were also shown to be competent at pertechnetate reduction.…”
Section: Sy 103mentioning
confidence: 99%
“…Noble metals. Simulant work has indicated that in the presence of the noble metal precipitates, organic complexants themselves can reduce pertechnetate to form alkaline soluble technetium compounds (Bernard et al 2001). …”
Section: The Presence Of Soluble Transuranic Elementsmentioning
confidence: 99%
“…Reduced forms of Tc can form complexes with these chelators, and they have characteristic UV-Vis absorbance spectra [38]. If catalytic metal salts are also present, TcO 4 − may be quantitatively reduced to TcO 2 [39].…”
Section: Effects Of Chelating Agentsmentioning
confidence: 99%